Effect of Roselle calyces extract on the chemical and sensory properties of functional cupcakes - A.R. Abdel-Moemin (Food Science and Human Wellness)
Roselle calyces (RC) are a major crop for export and used to make a common drink in Egypt. Dried RC are commercially available and appreciated to obtain concentrated extracts which might be used in the food and pharmaceutical industries for color and heath benefits. The objective of this research was to determine the chemical and the sensory properties of cupcakes formulated with Roselle calyces extract (RCE). Proximate analysis, anthocyanins, ascorbic acid, titrable acidity, % retaining of anthocyanins, color and sensory evaluations were done. RC cupcakes had high sensory scores (P < 0.05) compared to control cupcakes. The parameter a* was significantly red in the RC cupcakes compared to control cupcakes along with 77% retaining of anthocyanins. The consumption of 100 g of the RC cupcakes would provide 465 mg/100 g dry matter anthocyanin that is more than 2 folds of the minimum average of the daily intake of anthocyanins for Americans, along ∼1/3 of the daily dietary fiber intake to achieve fiber adequacy according to the Scientific Advisory Committee on Nutrition. RC cupcake can be a functional food and would have a “clean” label with cost effective advantage.